Students' Perception on Formative and Shared Assessment: Connecting two Universities through the Blogosphere - Daniel Martos-Garcia; Oidui Usabiaga; Alexandra Valencia-Peris (Springer, 2017)
The aim of this study was to evaluate differences in physical education students' perception on an educational innovation based on formative and peer assessment through the blogosphere. The sample was made up of 253 students from two Spanish universities. Data was collected using a self-reported questionnaire and t tests were employed in order to find differences among students' groups. Results show significant differences in almost all of the items on which the students were questioned. Basque students were more satisfied with the assessment tool used than the Valencian students. Students found the blogosphere more active, meaningful, functional and motivating and that it made for collaborative learning in comparison to other traditional evaluation methods. They also showed disapproval related to the demands on attendance, continuity and the greater effort required. For future occasions, negotiation about assessment criteria with the students should be implemented right at the very start of the course.